Energy Transformation and Entropy Investigation in the Nanofluid Composed by γ-Nanomaterial Over a Permeable Convective Surface With Solar Thermal Radiation: A Numerical Analysis - Adnan,; Ashraf, Waqas; Junaid Anjum, Hafiz; Khan, Ilyas; Mousa, Mohamed; Mehrez, Sadok (Frontiers in Energy Research, 2022)
The modern world moves toward new inventions by using nanotechnology and solar thermal radiations. On Earth, the Sun is the leading source of solar energy having a wider range of applications. These can be found in solar power plates (SPP), photovoltaic cells (PVC), solar thermal aircraft, and photovoltaic lighting. Therefore, the study is organized to analyze and improve the energy efficiency in the nanofluid over a permeable convective surface. The used nanofluid is synthesized by γ-nanoparticles and water. A theoretical experiment is conducted and a constitutive relation for the momentum and energy modeled. The model was tackled numerically and obtained the results for the velocity and energy transformation under varying effects of the pertinent flow parameters. From the study, it is observed that energy efficiency of the surface could be improved in the presence of solar thermal radiations, viscous dissipation, and convective heat conduction.